2020
DOI: 10.3390/s20082419
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Photoemission on p-Type GaAs Using Surface Acoustic Waves

Abstract: We demonstrate that photoemission properties of GaAs photocathodes (PCs) can be altered by surface acoustic waves (SAWs) generated on the PC surface due to dynamical piezoelectric fields of SAWs. Simulations with COMSOL indicate that electron effective lifetime in p-doped GaAs may increase by a factor of 10x to 20x. It implies a significant, by a factor of 2x to 3x, increase of quantum efficiency (QE) for GaAs PCs. Essential steps in device fabrication are demonstrated, including deposition of an additional la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…They demonstrated that the inner-crystal polarization potential generated by the flexoelectric field could be used to modulate the metalsemiconductor interface Schottky barrier and further tune charge-carrier transport. These findings provide prospects for semiconductor physical devices and electromechanical applications [26][27][28][29], and promote new research on semiconductor-based flexoelectricity technology [30,31].…”
Section: Introductionmentioning
confidence: 77%
“…They demonstrated that the inner-crystal polarization potential generated by the flexoelectric field could be used to modulate the metalsemiconductor interface Schottky barrier and further tune charge-carrier transport. These findings provide prospects for semiconductor physical devices and electromechanical applications [26][27][28][29], and promote new research on semiconductor-based flexoelectricity technology [30,31].…”
Section: Introductionmentioning
confidence: 77%
“…F I G U R E 7 Room temperature PE characteristics of: (1) untreated GaAs substrate, (2) as-grown GaAs:Ge structure, (3,4) GaAs substrate and GaAs:Ge structure annealed at 650 • C for 60 minutes, respectively…”
Section: Photoemission Characterizationmentioning
confidence: 99%
“…It is commonly used for generating electron beams for applications such as electron microscopes, free electron lasers, and other particle accelerators. [1][2][3] It can also be used for devices of more modest performance requirements such as simple diodes, but then the cost of the photocathodes must be reduced. The energy of the light must be equal to or higher than the work function Φ of the emitting material so for many applications, high-energy ultra-violet (UV) light is required.…”
Section: Introductionmentioning
confidence: 99%
“…It is a promising method for achieving single photon sources and single photon detectors 17 22 This makes use of the fact that, in a semiconductor piezoelectric material, the electrons and holes are separated by surface acoustic waves (SAWs) that have periodical potential, as shown in Fig. 1(a) 16 , 23 …”
Section: Introductionmentioning
confidence: 99%